Supramolecular Self‐Assembly of DNA with a Cationic Polythiophene: From Polyplexes to Fibers. Issue 6 (22nd February 2019) - Leclercq, Maxime; Rubio‐Magnieto, Jenifer; Mohammed, Danahe; Gabriele, Sylvain; Leclercq, Laurent; Cottet, Hervé; Richeter, Sébastien; Clément, Sébastien; Surin, Mathieu
Abstract: Cationic polythiophenes constitute an interesting class of polymers for prospective applications in imaging, gene delivery and biosensing, as they combine solubility in aqueous media and have sensitive optical properties for the detection of biomolecules such as DNA. Here, we study the supramolecular self‐assembly of poly[3‐(6'‐(trimethylphosphonium)hexyl)thiophene‐2, 5‐diyl] (P3HT‐PMe3 ) with different types of DNA such as single‐stranded oligonucleotides or long genomic DNA. Self‐assembly in buffered aqueous solution yields polyplexes (polymer/DNA complexes) with hydrodynamic radii ranging from 7 nm to around 25 nm, as observed by Taylor Dispersion Analysis. In these polyplexes, the achiral polymer presents chiroptical signals induced by supramolecular organization along chiral DNA. When the solution of long DNA/P3HT‐PMe3 is deposited on surfaces, tens of μm‐long fibers are formed by condensation of DNA and compaction of the polyplexes, as evidenced by microscopy techniques. Abstract : Cationic polythiophenes constitute an interesting class of polymers for prospective applications in imaging, gene delivery, and biosensing. Here, the supramolecular self‐assembly of poly[3‐(6'‐(trimethylphosphonium)hexyl)thiophene‐2, 5‐diyl] with different types of DNA, from single‐stranded oligonucleotides to long genomic DNA, is revealed. Polyplexes form in solution and tens of μm‐long fibers form on surfaces.